A novel model using mean platelet volume and neutrophil to lymphocyte ratio as a marker of nonalcoholic steatohepatitis in NAFLD patients: multicentric study. Issue 1 (January 2016) - Abdel-Razik, Ahmed; Mousa, Nasser; Shabana, Walaa; Refaey, Mohamed; ElMahdy, Youssif; Elhelaly, Rania; Elzehery, Rasha; Zalata, Khaled; Arafa, Mohammad; Elbaz, Sherif; Hafez, Mohamed; Awad, Mahmoud
Abstract : Background and aim: Nonalcoholic fatty liver disease (NAFLD) is a leading cause of progressive and chronic liver injury. Mean platelet volume (MPV) and the neutrophil–lymphocyte ratio (N/L ratio) may be considered cheap and simple markers of inflammation in many disorders. We aimed to investigate the clinical utility of MPV and the N/L ratio to predict fibrosis in NAFLD patients and the presence of nonalcoholic steatohepatitis (NASH). Materials and methods: A total of 873 patients with biopsy-proven NAFLD and 150 healthy controls were included. Patients were divided into two groups: non-NASH group ( n =753) and NASH group ( n =120). Liver biopsy, MPV, lymphocyte, and neutrophil counts were registered; the N/L ratio was calculated. Proinflammatory cytokines (tumor necrosis factor-α and interleukin-6) were measured by an ELISA. Results: NASH patients had higher MPV compared with non-NASH patients (10.9±1.8 and 9.5±1.6 fl, respectively, P <0.001). MPV correlated positively with the NAFLD activity score, proinflammatory cytokines, and C-reactive protein (CRP) ( P <0.001). Patients with advanced fibrosis (F3–4) had increased MPV (11.3±0.9 fl) compared with patients with early fibrosis (F1–2) (10.2±0.8 fl, P <0.001). NASH patients had an increased N/L ratio compared with non-NASH cases (2.6±1.1 and 1.9±0.7 fl, respectively, P <0.001). The N/L ratio correlated positively with NAFLD activity score, proinflammatory cytokines, and CRP ( P <0.001). In addition, patients with advanced fibrosis (F3–4) had an N/L ratio (2.5±1.1) comparable with that of patients with early fibrosis (F1–2) (1.8±0.9) ( P <0.001). Conclusion: MPV and the N/L ratio were elevated in NASH patients versus non-NASH cases, and in patients with advanced fibrosis (F3–4) versus early fibrosis (F1–2). They can be used as noninvasive novel markers to predict advanced disease.